إجراءات المراجعة المستخدمة في تقييم استمرارية المشروع دراسة حالة على شركة مراجعة وطنية - الأمين, ماهر; يوزباشي, هلا (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف البحث إلى تحديد مؤشرات الشك التي تساعد مراجعي الحسابات في سورية على التعرف على وجود شك جوهري في قدرة الشركة على الاستمرار، ومدى ملاءمة هذه المؤشرات مع المؤشرات المحددة في معيار المراجعة الدولي رقم570.والتعرف على إجراءات المراجعة الإضافية التي يتبعها مراجعو الحسابات في سورية في حال وجود أحداث أو ظروف قد تؤثر على الاستمرارية، ومدى ملاءمة هذه الإجراءات مع الإجراءات المحددة في معيار المراجعة الدولي رقم 570 .توصلت الدراسة إلى أن وجود خسائر مالية متكررة وزيادة المطلوبات المتداولة على الموجودات المتداولة هو من أهم المؤشرات التي تساعد مراجعي الحسابات العاملين في شركة المراجعة محل الدراسة في تقييم الاستمرارية. This research aims to define doubt indicators that help auditors in Syria to know the existence of significant doubt about the ability of an entity to continue as a going concern, and how much these indicators are close to the indicators defiend in the international standards auditing No 570. And know the additional auditing procedures that are followed by auditors in Syria in case of the existence of any events or circumstances that influence the going concern , and how much these procedures are close to the indicators defined in the international standards auditing No 570. This study concluded that existence of frequent financial losses and the increase of current liabilities over current assets are considered the most important indicators that help auditors working in auditing company under study in evaluating going concern.